2010
DOI: 10.1088/0004-637x/716/1/154
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Rain as a Marker for Coronal Heating Mechanisms

Abstract: Reported observations in Hα, Ca II H and K or or other chromospheric lines of coronal rain trace back to the days of the Skylab mission. Offering a high contrast in intensity with respect to the background (either bright in emission if observed at the limb, or dark in absorption if observed on disk) these cool blobs are often observed falling down from high coronal heights above active regions. A physical explanation for this spectacular phenomenon has been put forward thanks to numerical simulations of loops … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

37
168
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(208 citation statements)
references
References 72 publications
37
168
3
Order By: Relevance
“…Recent observations from the Solar Optical Telescope (SOT) on board Hinode, the Interface Region Imaging Spectrograph (IRIS), and ground-based observatories such as the Swedish Solar Telescope have demonstrated coronal rain is a common occurrence (e.g. Antolin et al 2010;Antolin & Rouppe van der Voort 2012;Kleint et al 2014;Antolin et al 2015;Straus et al 2015). Coronal rain accelerates towards the solar surface at overall average values of around 80±30 m s −2 (Antolin & Rouppe van der Voort 2012), which is considerably smaller than solar gravitational acceleration, even when taking into account the effective gravity in the direction of the guiding magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations from the Solar Optical Telescope (SOT) on board Hinode, the Interface Region Imaging Spectrograph (IRIS), and ground-based observatories such as the Swedish Solar Telescope have demonstrated coronal rain is a common occurrence (e.g. Antolin et al 2010;Antolin & Rouppe van der Voort 2012;Kleint et al 2014;Antolin et al 2015;Straus et al 2015). Coronal rain accelerates towards the solar surface at overall average values of around 80±30 m s −2 (Antolin & Rouppe van der Voort 2012), which is considerably smaller than solar gravitational acceleration, even when taking into account the effective gravity in the direction of the guiding magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Coronal rain accelerates towards the solar surface at overall average values of around 80±30 m s −2 (Antolin & Rouppe van der Voort 2012), which is considerably smaller than solar gravitational acceleration, even when taking into account the effective gravity in the direction of the guiding magnetic field. Various mechanisms have been proposed to explain this, including plasma pressure effects (Antolin et al 2010), ponderomotive force when transverse oscillations are present (Verwichte et al 2017) and the combination of plasma pressure and magnetic tension forces (Mackay & Galsgaard 2001;Kohutova & Verwichte 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang & Li (2009) analysed 26 coronal rain events in Ca II filtergrams using images of the Solar Optical Telescope (SOT) on board Hinode and found two types of blobs: fast and slow, with average speeds of 72 km s −1 and 37 km s −1 , respectively. Antolin et al (2010) analysed SOT/Hinode Ca II H line data and found that the blobs started to fall down from the height of 60-100 Mm with low (∼30-40 km s −1 ) speed, but accelerated to high (∼80-120 km s −1 ) speed in the lower parts of loops. The accelerations were found to be on average substantially lower than the solar gravity component along the loops.…”
Section: Introductionmentioning
confidence: 99%
“…There is some observational evidence of nanoflares in the coronal X-ray emission (Katsukawa & Tsuneta 2001;Schmelz et al 2009). The bright points in coronal EUV lines (Madjarska et al 2003;Tian et al 2008) and the phenomenon of coronal rain (De Groof et al 2004;Antolin et al 2010) may also be associated with nanoflares. But the firm observational evidence of nanoflare heating of the solar corona is still absent.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the hot plasma then can be quickly cooled down to the transition region or chromospheric temperatures owing to "catastrophic cooling" (Antiochos & Klimchuk 1991;Schrijver 2001;Müller et al 2003Müller et al , 2004Karpen et al 2006;Klimchuk et al 2010). The resulting dense and cool plasma blobs may then be attracted by gravity, slide down along the magnetic field lines, and result in "coronal rain" (De Groof et al 2004;Antolin et al 2010). In addition, such a compressible perturbation would generate an outgoing magnetoacoustic wave (Longcope & Priest 2007), which can be subject to steepening.…”
Section: Introductionmentioning
confidence: 99%